Per una storia delle pratiche didattiche in prospettiva europea: il caso del “metodo normale” - Monica Ferrari (Studi sulla Formazione)
The “normal method”, as it has been defined in its making, is a very interesting issue for those eager to study, in a diachronic and comparative way at a European level, some aspects of educational and didactic practices in relation to the development of educational institutions and their “communities of practice”. Starting from the example of the “normal method”, analyzed also thanks to dictionaries and studies that have influenced the pedagogical debate in the contemporary age, this essay emphasizes the need to conduct case studies capable of reconstructing particular aspects of a cultural history that has contributed to organize specific didactic and institutional patterns in Europe.